2009
DOI: 10.1590/s1516-44462009000300009
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of psychopathology in offspring of bipolar women from a Brazilian tertiary center

Abstract: Resultados: Os filhos de mães bipolares tiveram duas vezes mais chance de ter um ou mais diagnósticos de Eixo I [Razão de Prevalência = 2,11 (95% IC: 1,42) e p = 0,003] e 2,8 vezes maior risco de ter transtornos de ansiedade [Razão de prevalência = 2,83 (95% IC: 1,78)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 34 publications
(35 reference statements)
0
34
0
9
Order By: Relevance
“…16 Petresco and colleagues demonstrated that the offspring of bipolar mothers had higher prevalence of ADHD (11.6%) compared to the offspring of control mothers (4.7%). 17 We also found high rates of ADHD in offspring of parents with BP and offspring with BP in the Pittsburgh Bipolar Offspring Study (BIOS). 13,18 However, these studies were limited by one or more of the following limitations: lack of longitudinal prospective evaluation of the ADHD symptomatology, small sample sizes, not taking into account the effects of several factors that may have affected the outcome (e.g., socioeconomic status, pubertal status, and children’s comorbid disorders), and control groups consisting of offspring of healthy parents only.…”
Section: Introductionmentioning
confidence: 70%
“…16 Petresco and colleagues demonstrated that the offspring of bipolar mothers had higher prevalence of ADHD (11.6%) compared to the offspring of control mothers (4.7%). 17 We also found high rates of ADHD in offspring of parents with BP and offspring with BP in the Pittsburgh Bipolar Offspring Study (BIOS). 13,18 However, these studies were limited by one or more of the following limitations: lack of longitudinal prospective evaluation of the ADHD symptomatology, small sample sizes, not taking into account the effects of several factors that may have affected the outcome (e.g., socioeconomic status, pubertal status, and children’s comorbid disorders), and control groups consisting of offspring of healthy parents only.…”
Section: Introductionmentioning
confidence: 70%
“…In adults, the rates are around 5 to 10%, suggesting a larger genetic component in the early-onset form of BD. [42][43][44] In naturalistic studies of BD among children and adolescents, the recovery rates are high (70 to 100%), but the recurrence rate in 2 to 5 years is up to 80%. [45][46][47] Moreover, most of the time these patients experienced subsyndromal and syndromal mood symptomatology and frequent mood fluctuations, as reported in the Course and Outcome of Bipolar Youth (COBY, n=263) 2-year followup study.…”
Section: Epidemiologymentioning
confidence: 99%
“…An important consideration is whether the reviewed studies are developmentally informative, with regard to (i) what developmental patterns of DRT are evident in O‐BD and (ii) whether these perturbations of early development portend impaired functioning for O‐BD compared to low‐ or high‐risk groups. Although many of the dimensional studies were cross‐sectional and included a wide range of ages (e.g., , , ), making it difficult to characterize DRT in specific developmental periods, an imperative consideration also is the developmental window being assessed. Ideally, elevations in DRT should be examined at developmentally relevant assessment points, such as during age‐salient developmental tasks, developmental transitions or points in development when pathological conditions associated with DRT emerge .…”
Section: Resultsmentioning
confidence: 99%
“…The most consistently used dimensional approach, utilized by eight of the studies listed in Table to evaluate DRT, was to examine raw or T ‐scores from the Thought Problems (TP) scale from the CBCL, Youth Self‐Report (YSR), Young Adult Self‐Report (YASR), Young Adult Behavior Checklist (YABCL), and Teacher‐Report Form (TRF) . The Achenbach scales are empirically derived from factor analytic techniques and have demonstrated sound internal consistency and test–retest reliability (e.g., r = 0.74 over a two‐week interval) .…”
Section: Methodsmentioning
confidence: 99%